Autonomic Imbalance Induced Breakdown of Long-range Dependence in Healthy Heart Rate - Aoyagi, N.; Struzik, Z. R.; Kiyono, K.; Yamamoto, Y. (Methods of Information in Medicine, 2007)
Objectives: The investigation of the relation between the long-range correlation property of heart rate and autonomic balance.Methods: An investigation of the fractal scaling properties of heart rate variability was carried out by using detrended fluctuation analysis (DFA). Eleven healthy subjects were examined for two consecutive days, which included usual daily activity, strenuous prolonged experimental exercise, and sleep. We also considered two patient groups with autonomic dysfunction characterized by selective sympathetic and parasympathetic dominance.Results: Robust long-range dependence in heart rate is observed only in the state of usual daily activity, characterized by normal heart rate typical of balanced autonomic sympathetic and parasympathetic regulation. This confirms the previously postulated behavioral independence of heart rate regulation, but reveals that the occurrence of 1/f, long-range dependence is restricted to only the state of autonomic balance. Both the sympathetic dominant high heart rate state, realized during strenuous experimental exercise, and the parasympathetic dominant low heart rate state, prevalent in (deep) sleep, are characterized by uncorrelated, near white-noise-like scaling, lacking long-range dependence.Conclusion: Remarkably, the breakdown of the long-range correlations observed in healthy heart rate in the states of sympathetic and parasympathetic dominance is in stark contrast to the increased correlations which have previously been observed in neurogenic parasympathetic and sympathetic dominance in patients suffering from primary autonomic failure and congestive heart failure, respectively. Our findings further reveal the diagnostic capabilities of heart rate dynamics, by differentiating physiological healthy states from pathology.
Keywords: Autonomic balance; long-range correlation; detrended fluctuation analysis